METAFORA KEBUDAYAAN CINA DALAM IDIOM BAHASA CINA - Budi Santoso (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2007)
Metaphor is commonly used to express idea or concept through short words. It is characterized by the comparison of two things in common. One of metaphor forms is idiom. In Chinese, idiom is an ancient expression taken from poems, classical books, myths or folktales. Therefore, sufficient cultural knowledge and historical backgroud of the idiom is essential in understanding Chinese idiom. It can be said that Chinese idioms are reflections of Chinese Culture metaphor.